Superando una vieja enemistad: El Principio de Legalidad, la Lex Constructionis y la supletoriedad coactiva en los contratos de Obra Pública - Collantes Rojas, Christian (2023)
In this article, the author intends to demonstrate, through specific cases, that the custom in the construction sector (Lex Constructionis) is increasingly immersed in the Public Administration, being recognized as a supplementary regulatory source in public works contracts, by the State Procurement Law. Overcoming the idea that the custom does not has a place in public law. Likewise, it seeks to demonstrate that the responsible and reasonable importation of custom in the construction industry has not violated in any way the legality that governs public works contracts, but, on the contrary, has nurtured and strengthened it, in benefit of the public interest and of the contract administrators, who are, ultimately, the end users of the public infrastructure.